PELAKSANAAN FUNGSI PENGAWASAN DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) TERHADAP PENGANGKUTAN SAMPAH DI KOTA PEKANBARU TAHUN 2023 - Akmal, Yonda Satria; Nasution, Hazqon Fuadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The problem of waste transportation in Pekanbaru City in 2023 remains a pressing environmental issue due to the suboptimal performance of the local government. This study aims to analyze the implementation of the Pekanbaru City Regional Representative Council (DPRD)'s oversight function regarding waste transportation. The approach used was descriptive qualitative, with data collection techniques through interviews and documentation, involving informants from the DPRD, the Environment and Sanitation Agency (DLHK), and the community. The research analysis utilized Siagian's oversight theory in Ardansyah (2014), which distinguishes between direct and indirect supervision. The results indicate that DPRD supervision is implemented through Commission IV in coordination with the DLHK. Direct supervision is conducted through field visits and unannounced inspections to follow up on findings of delays in waste transportation, which cause backlogs at several locations. Meanwhile, indirect supervision is carried out through working meetings and discussions of the DLHK's Government Agency Performance Report (LKjIP) to request explanations and ensure follow-up on field issues. This study concludes that the DPRD's oversight function has been implemented but has not been optimal in ensuring the effectiveness of waste transportation in Pekanbaru City. Keywords: DPRD, supervision, waste transportation, Pekanbaru City, DLHK.